The role of bacterial infection in the pathogenesis of psoriasis - N. A. Slesarenko; S. R. Utz (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents the results of numerous studies confirming the involvement of bacterial agents in the psoriatic process manifestation as triggering factors. The article discusses potential pathogenic mechanisms of the participation of bacterial superantigens in the initiation of a cascade of immunological reactions resulting in the hyperproliferation of keratinocytes. The expediency of using antibacterial agents as a part of a complex therapy of different forms of the disease is discussed.